Use of Electrochemical Noise Measurements for Determining the Rate of Corrosion and the Surfactant Aggregate Transition Concentration at the Mild Steel–Liquid Interface - Dong Y. Ryu; Michael L. Free (Adsorption Science & Technology)
Corrosion events such as uniform corrosion, localized corrosion and hydrogen evolution at metal–liquid interfaces can be monitored by a combination of electrochemical noise and corrosion inhibition measurements. The effective prediction of corrosion inhibition by surfactants can be accomplished by determining the surfactant aggregation transition concentration (atc) at the metal–liquid interface. This paper discusses the use of electrochemical noise measurements for determining the atc as well as the rate of corrosion.